Effect of decocted turmeric on performance, hematological parameters and carcass traits of broiler chickens - Isroli, I.; Yudiarti, T.; Widiastuti, E.; Sugiharto, S. (Diponegoro University, 2017)
This study aimed to investigate the effect of decocted turmeric on performance, haematological parameters and carcass traits of broilers. Broiler chicks at 11 days of age were allotted to five groups, including T0 (birds drinking 100% water), T1 (25% decocted turmeric + 75% water), T2 (50% decocted turmeric + 50% water), T3 (75% decocted turmeric + 25% water) and T4 (100% decocted turmeric). The study was arranged based on a completely randomized design (CRD), parameters investigated was performance and blood chemistry (leukocyte, total protein, albumin, globulin, uric acid, glucose). The data were subjected to analysis of variance at 5% probability. Decocted turmeric did not affect weight gain, feed and water consumption and feed conversion ratio of broilers. Lymphocytes proportion was higher (P<0.05) in T1, T2 and T4 than in T0 and T3 birds. The heterophils to lymphocytes ratio was lower (P<0.05) in birds receiving decocted turmeric than control. Globulin concentration and albumin to globulin ratio were higher and lower (P<0.05), respectively, in serum of T2, T3 and T4 than T0 and T1 birds. The proportion of heterophils and concentration of serum total protein, albumin, uric acid and glucose were not different among treatments. The weight of breast meat was higher and lower (P<0.05) in T3 and T4 birds, respectively, compared to the control. In conclusion, providing decocted turmeric through drinking water helped to improve stress responses and increased the weight of breast meat of broiler chickens.